The Effectiveness of Using the Quizizz Tool in Teaching Directed Composition (An Experimental Study Among Students at Al-Najah Senior High School Bogor - Qotrunnada Qotrunnada; Siti Uriana Rahmawati; Raswan Raswan (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2025)
This study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The research sample consisted of 50 eleventh-grade students divided into two groups: an experimental group of 25 students from the Science and Technology class and a control group of 25 students from the Health class. Each group underwent two tests, namely a pre-test and a post-test. The experimental group received special treatment through the use of Quizizz as a tool for teaching guided composition. Data collection techniques included tests, interviews, and observations. Data were analyzed using various statistical tests, including the independent sample t-test, normality test, and N-Gain test to measure the effectiveness of using Quizizz in teaching guided composition. The post-test results showed that the experimental group achieved an average score of 84.2, while the control group scored 56.8. Based on the t-test analysis using SPSS, the Sig (2-tailed) value was 0.000, which is lower than the 0.05 threshold. This indicates that the null hypothesis (Ho) is rejected, while the alternative hypothesis (Ha) is accepted, leading to the conclusion that the use of Quizizz significantly improves learning outcomes. Additionally, the average N-Gain score of 71.65%, which falls within the 56-75% range, suggests that Quizizz is an effective tool for teaching guided composition.Keywords: Quizizz Method, Teaching Guided Composition, Writing kill.مستخلص البحثاستخدمت هذه الدراسة نهجًا كميًا مع طريقة شبه تجريبية وتصميم مجموعة التحكم غير المتكا?ئة. تأل?ت عينة البحث من 50 طالب ?ي الص? الحادي عشر مقسَّمين إلى مجموعتين: مجموعة تجريبية تضم 25 طالبًا من الص? الحادي عشر للعلوم والتكنولوجيا ومجموعة ضبيطة تضم 25 طالبًا من الص? الحادي عشر الصحة. خضعت كل مجموعة لاختبارين، وهما الاختبار القبلي والاختبار البعدي. تلقت المجموعة التجريبية معاملة خاصة ?ي شكل استخدام وسيلة Quizizz ?ي تعليم الإنشاء الموجه. تشمل تقنيات جمع البيانات الاختبارات والمقابلة والمراقبة. تم تحليل البيانات باستخدام العديد من صيغ الاختبار، وهي اختبار العينة المستقلة T، واختبار الحالة الطبيعية، واختبار N-Gain لقياس ?عالية استخدام وسيلة Quizizz ?ي تعليم الإنشاء الموجه. أظهرت نتائج ما بعد الاختبار أن المجموعة التجريبية حصلت على متوسط درجة 84،2، بينما حصلت المجموعة الضابطة على 56،8. استنادًا إلى اختبار t باستخدام SPSS، تم الحصول على Sig (2-ذيل) 0،000 قدرها 0،000 ، وهي أقل من المعيار 0،05. يوضح هذا أن ال?رضية الص?رية (Ho) مر?وضة و ال?رضية البديلة (Ha) مقبولة، لذلك يمكن استنتاج أن استخدام وسيلة Quizizz يحسن بشكل كبير نتائج التعلم. بالإضا?ة إلى ذلك، يشير متوسط نتيجة N-Gain البالغ 71،65٪، والذي يتراوح بين 56-75، إلى أن استخدام وسيلة Quizizz ?عال ?ي تعليم الإنشاء الموجه. الكلمات الم?تاحية : وسيلة Quizizz، تعليم الإنشاء الموجه، مهارة الكتابة.